Stability of Stem form Quotient in Clones of Eucalyptus camaldulensis Dehnh across Southern India - Nair, Smitha G.; Veerasamy, Sivakumar; Vijayaraghavan, A.; Suresh, G.; Anees, A.; Vinothkumar, A.; Yuvaraj, T. (Indian Forester, 2021)
Stem taper, often quantified as form quotient or form factor, is an index of the narrowing of tree trunk with respect to its height. It is a heritable character influenced by environment. Single tree volume calculations without taking the Form factor into account may not give accurate values. Use of a general form factor instead of specific form factor for each clone, even in the case of clear boles like Eucalyptus camaldulensis may result in an overestimation or underestimation of volume. This is significant as E. camaldulensis is a pulp wood species and form quotient near to one indicates lesser taper and higher pulpwood recovery. This study explores the variation in form quotient across locations for E. camaldulensis clones and the genotype X environment interaction (GEI) effects on form quotient across four sites viz., Marakkanam, Ariyalur, Tirupati and Karaikal.